Management and organization of innovative activity of the enterprises. - Tumbai Sydykova, Zh. A. O. D. (Journal of Economic Research & Business Administration, 2016)
Independent Kazakhstan took a step in a new economic era, that is innovative industrially to development. Idea of creation of the «clever economy» based on knowledge in the future. Businessmen of Kazakhstan uses foreign scientific and technological skill in activity of an innovation. The state in return uses a lot of the stimulating measures for development of the innovation environment. Nevertheless favorable conditions for stimulation of innovative activity it has to be created. Now all responsibility lie to the government, that is domestic producers should be supported through legal bases, national the fund and institutes of development should be supported surplus of production is formed. In commission of innovative projects it is necessary to form special innovative banks and venture bank activity.We will consider problems in development of innovative business, scientific and scientific researches demands more and more risk and expenses.